Application of Raman spectroscopy and chemometrics for quality controls of fats and oils: a review - Windarsih, Anjar; Lestari, Lily Arsanti; Erwanto, Yuny; Anggita Rosiana, Putri; Irnawati, Irnawati; Ahmad Fadzillah, Nurrulhidayah; Nuning, Rahmawati; Abdul, Rohman (Taylor and Francis Ltd., 2021)
Edible fats and oils, composed of triacylglycerols (TAG) and some minor components having beneficial effects to human health such as lipid-soluble vitamins, carotenoids, and phenolics compounds, are essential to human diets because they are good energy sources. Some edible fats and oils had high price in the market which are lucrative to be adulterated with lower priced ones to gain the economical profits. Therefore, it is essential to assure the quality of edible fats and oils to fulfill the requirements and to detect the possibility of adulterated products using reliable analytical methods. Vibrational spectroscopies consisting of infrared and Raman are widely applied for analysis of edible fats and oils. In this review, Raman spectroscopy combined with chemometrics has been highlighted for quality control and authentication analysis of edible fats and oils either in raw materials or in food products.